Autosomal Dominant ANO5-Related Disorder Associated With Myopathy and Gnathodiaphyseal Dysplasia. (August 2021) - Shaibani, Aziz; Khan, Shaida; Shinawi, Marwan
Abstract : Objective: To investigate the molecular basis of muscle disease and gnathodiaphyseal dysplasia (GDD) in a large kindred with 11 (6 women and 5 men) affected family members. Methods: We performed clinical assessment of 3 patients and collected detailed clinical and family history data on 8 additional patients. We conducted molecular genetic analyses on 5 patients using comprehensive neuromuscular disorder panels, exome sequencing (ES), and targeted testing for specific genetic variants. We analyzed the segregation of the muscle and bone phenotypes with the underlying molecular cause. Results: The unique clinical presentation of recurrent episodes of rhabdomyolysis associated with muscle cramps, hyperCKemia, muscle hypertrophy, with absent or mild muscle weakness, as well as cemento-osseous lesions of the mandible, with or without bone fractures and other skeletal abnormalities, prompted us to look for the underlying molecular cause of the disorder in this kindred. Molecular testing revealed a missense variant in anoctamin 5 ( ANO5 ) designated as c.1538C>T; p.Thr513Ile, which was previously described in a large kindred with GDD. In silico analysis, searching publicly available databases, segregation analysis, as well as functional studies performed by another group provide strong evidence for pathogenicity of the variant. ES data in the proband excluded the contribution of additional genetic factors. Conclusions: This report described the coexistence of muscle and bone phenotypes in the same patients with ANO5-related disorder. Our data challenge recent results that suggested complete dichotomy of these phenotypes and the proposed loss-of-function and gain-of-function mechanisms for the skeletal and muscle phenotypes, respectively.